The old-boy network and the quality of entrepreneurs - Mehmet Bac; Eren Inci (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study a model of network formation and start-up financing with endogenous entrepreneurial type distribution. A hub firm admits members to its network based on signals about entrepreneurs' types. Network membership is observable, which allows lenders to offer different interest rates to network and stand-alone entrepreneurs. We show that a network outcome can display a smaller number of high-type entrepreneurs even though the network is neither nepotistic nor informationally disadvantaged. While a welfare-improving network can emerge as a technically stable or unstable equilibrium, one that decreases welfare is always formed by a technically unstable equilibrium. However, the adverse welfare effects of a network and its corresponding type configuration may persist because ex-post high type entrepreneurs prefer to stay high type whereas those who wish to become high-type may need some time to react.
Keywords: D82; D85; L26; 330; entrepreneur; network; start-up financing; Entrepreneurship-Ansatz; Business Network; Unternehmensgründung; Risikokapital; Soziales Netzwerk; Spieltheorie; Wohlfahrtseffekt; Theorie